Colección y tratamiento del Drenaje Acido de Minas de la Unidad Minera La Zanja del Grupo Buenaventura - Custodio Sánchez, Alexis Rafael (2023)
The investigation has been developed based on the treatment of Acid Mine Drainage (AMD) naturally emitted within the operations of the La Zanja mining unit, said Acid Drainage is the result of the oxidation of metal sulfides, in the presence of atmospheric oxygen. and water being one of the main sources of contamination of surface and groundwater, these drainages are toxic to varying degrees for man, fauna and vegetation because, having a low pH, they contain a large amount of solids in suspension with a high content of sulfate and metals (Fe, Al, Mn, Zn, Cu, Pb, Hg, Cd, Ni), of the order of several hundred milligrams per liter. For the treatment of DAM, active treatment methods are used that consist of treating with alkaline chemical reagents to raise the pH, neutralize the acidity and precipitate the metals, being the HDS process (high density sludge) used in the San Pedro Sur plant and It is characterized by the use of calcium oxide to prepare the milk of lime and precipitate metals as insoluble hydroxides in a pH range that is usually between 6.5 and 9.5. Ferrous iron becomes ferrous hydroxide at a pH greater than 7.5, manganese becomes insoluble when pH is above 9 and aluminum precipitates as hydroxide at pH above 7. Sampling before and after treatment for the measurement of physical-chemical parameters as well as the analysis of total and dissolved metals must be carried out in accordance with the Water and Effluent Monitoring Protocol published by MINEM, although the values of pH were low and the heavy metal contents were high, it was achieved that the effluent values obtained after the treatment are in accordance with the standards established for its discharge or reuse and must be compared according to the Maximum Permissible Limits for the discharge of liquid effluents from Mining – Metallurgical Activities approved under D.S. No. 010-2010-MINAM